Investigation of toxicity, antimicrobial activity and cough treatment of products produced from Pouzolzia zeylanica plants growing in Vietnam - Nguyen, Duy Tan; Vo, Thi Xuan Tuyen (Penerbit Universiti Kebangsaan Malaysia, 2020)
Pouzolzia zeylanica (L.) Benn is one of the medicinal plants that possess a lot of bioactive compounds with potential for therapeutics. These plants have usually been consumed in traditional way despite its efficacy and safety proven. The objectives of this study were to evaluate the toxic and pharmacological effects of concentrated and spray-dried extract of Pouzolzia zeylanica. The plant is popular for its auxiliary substances in the treatment of cough; however, the information about the safety of their usage need to be explored. In the study, the antibacterial ability of respiratory, acute oral toxicity, effects of reducing sputa and cough symptom were evaluated. The antibacterial ability of the test product was assessed on 5 strains of respiratory tract pathogenic bacteria by minimum inhibitory concentration (MIC) method. The acute oral toxicity, effect to reduce sputum and cough treatment was tested in mice through capsaicin model following standardized methods. It was observed that both products were not causing acute oral toxicity. Pouzolzia zeylanica spray-dried powder had antibacterial activity on Streptococcus pyogenes with MIC of 50 mg/mL. Dose, which used (6 g/day converted in humans) showed effect on reducing sputa and cough symptom due to stimulation of cough model with capsaicin. In contrast, the concentrated product did not show antimicrobial activity in tested bacterial strains. Dose at 4 g/day converted in humans showed effect on reducing sputa in experimental mice that were affected with capsaicin. Nevertheless, the effect of it on cough symptoms caused by the capsaicin model was not typical in comparison with spray dried powder. Result showed that spray-dried powder did not exhibit acute oral toxicity, had antibacterial properties, reduced sputum and treated cough. This promises that it can be developed into a convenient instant tea product, supporting good health for consumers in preventing diseases.